Analysis of durability of hot-gas coatings and their choice for the restoration of parts of aircraft - Хімко, А.М.; Краля, В.О.; Якобчук, О.Є.; Бородій, В.М. (Proceedings of National Aviation University (archive), 2008)
It was made the analysis of wear-resistance of gas-thermal coating which were coated by plasma, detonation and impulse-plasma methods & working in the conditions of fretting-corrosion. For the choice of coating at renewal of elements of aviation technique, it is necessary to make complex analyses of the wear-resistance and other criteria which characterize operating properties of coating.